Optimalisasi Pendampingan Strategi Digital Marketing dan Peningkatan Daya Saing UMKM Jamur Tiram - Midi, Lamidi; Rahadhini, Marjam Desma; Rahmawati, Sisca Dian; Saputra, Leo Agung (Journal Of Human And Education (JAHE), 2024)
Lack of knowledge about how to develop an oyster mushroom bussiness is an obstacle for MSMEs. The problem faced by partners is that they have not implemented digital marketing to increase sales of oyster mushrooms in Gurung, Dukuh, Banyudono, Boyolali, namely Mr. Surya. The service aims to provide support to bussiness actors so that they can utilize digital marketing effectively to expand the market, increase profits and continue to complete professionally in facing the challenges of the digital era. The service was carried out using socialization, training, mentoring and evaluation methods. The first activity is socialization by providing understanding to partners about the importance of digital marketing strategies. Second, training in using technology in the form of taking product photos and videos. The third is assistance in untilizing social media, selecting social media and preparing routine content ideas in optimizing digital marketing. The fourth is an evaluation of the results of using digital marketing. Based on the results of the service, the interest of MSMEs in digital marketing has increased because it is able to increase profits and increase public appeal. It is hoped that with a digital marketing strategy, MSMEs can take advantage of the potential of the digital market to achieve great success.